(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The pulp is the inner part of the tooth, hidden deep in its center. It consists of various types of tissues, each of which performs certain functions, providing the tooth with vitality and sensitivity.